Genetic variation within two pulmonate limpet species, Siphonaria capensis and S. serrata along the South African coast - Seaman, Jennifer Ann (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 2003)
Dispersal rates are known to play a fundamental role in establishing the genetic structure found within a species. Dispersal in marine benthic invertebrates is largely dependent on life history strategy. The presence of pelagic larvae will potentially result in high dispersal within a species, while direct development limits dispersal. This study used two intertidal pulmonate limpet species to investigate the relationship between dispersal potential and genetic structure of populations. Siphonaria capensis produces benthic egg masses, which release pelagic larvae. These float in ocean currents before settling and metamorphosing into adults. S. serrata reproduces by direct development. The larvae hatch as completely metamorphosed juveniles after developing in an egg case not far from the parent. The high dispersal capacity of S. capensis pelagic larvae should result in high levels of within-population variation since individuals within a particular population may originate from several different populations. This should lead to high levels of gene flow along the coast and to low genetic differentiation among populations. On the other hand, the low dispersal potential of S. serrata should cause low levels of genetic variation within populations, as relatives will remain close to one another. Low levels of gene flow and high genetic differentiation among populations are expected in this species. In dealing with the relationship between life history strategy and population genetic structure in these two species, a series of indirect techniques was utilised. Multivariate analyses of the morphological variation within each species showed that variation in size was similar between the two species and largely governed by environmental factors. Variation in shell shape was largely under genetic control and supported the predictions made for each species. Variation in total proteins was relatively uninformative in terms of examining the differences between the two species. Allozyme analysis and mtDNA sequencing clearly showed differences between the species in terms of their population genetic structure. High levels of gene flow were found within S. capensis. This was strongly influenced by ocean currents, with the close inshore Agulhas current along the Transkei coast contributing to high levels of dispersal and hence gene flow. Low levels of gene flow occurred within S. serrata, resulting in low within-population variation and high among-population differentiation.
Keywords: Limpets -- South Africa; Pulmonata; Siphonaria; Limpets -- Genetics